Building Cooperation in a Competitive Industry: Sematech and the Semiconductor Industry - Browning, Larry D.; Beyer, Janice M.; Shetler, Judy C. (Academy of Management Journal, 1995)
This article presents the results of a grounded theory analysis of observation, interview, and archival data collected at SEMATECH, a research, development, and testing consortium in the semiconductor manufacturing industry. Three core categories of events and behaviors are described: (1) the factors underlying the consortium's early disorder and ambiguity, (2) the development of a moral community in which individuals and firms made contributions to the industry without regard for immediate and specific payback, and (3) the structuring that emerged from changing practices and norms as consortium founders and others devised ways to foster cooperation. We interpret results in terms of complexity theory, a framework for understanding change that has not been previously explored with detailed empirical data from organizations.